On the Move: Sharing Experience on the Bologna Process in the Arts - Butler, John (Amsterdam De Bevrijding, 2003)
Sharing experience on the Bologna Process in the arts is a publication of the European League of Institutes of the Arts (ELIA) in the framework of the Socrates Thematic Network Innovation in Higher Arts Education in Europe.Editors: Truus Ophuysen and Lars Ebert, ELIA Executive Office, Amsterdam, The NetherlandsThis Publication was supported by the European Commission. No part of this publication including the cover design, may be reproduced, stored or transmitted in any form or by any means without prior permission of the publisher.This publication reflects the views only of the authors.Printed: de Bevrijding, Amsterdam.Design: Joke Mestdagh, Robert van de Linde, Amsterdam.Copies of this handbook can be ordered from the ELIA Executive Office. Postal expenses will be charged.
Keywords: 21st Century (2001-2100); Music education